Low Competency Achievement in the Covid-19 Pandemic Era: Analysis of Application of Biology Learning Model - Nuraini, Latifah; Subali, Bambang; Heru, Nur; Daryono, Rihab Wit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Students are less active in online biology learning due to internet connection disturbances, so student learning outcomes are lower than face-to-face learning. This study aims to explore and analyze the learning model used by biology teachers in online learning, student competency achievement, and supporting and inhibiting factors that influence student competency achievement. This research is a descriptive research using survey method. The sample in this study used an accidental sample, namely a class XI biology teacher. The data analysis technique uses descriptive techniques by looking for the mode of answers given by respondents. The results showed that the biology online learning model used by the teacher was the PBL and guided inquiry learning models. The competency achievement of class XI high school students during online learning was still low, and the supporting factors for achieving student competency were the learning models often used, while the inhibiting factor was low student motivation. and not active in learning. The application of learning models is more optimized and encourages students to be more active when learning activities take place. The teacher must play a role in increasing student learning motivation so that it can foster student enthusiasm.